Leveraging the enrichment analysis from a genome-wide association study against epilepsy—focusing on the role of tryptophan catabolites pathway in patients with drug-resistant epilepsy - Chang, Alice Y. W.; Huang, Chin-Wei; Tsai, Ping-Lin; Liang, Chun-An; Liao, Wei Chen; Fu, Tzu-Fun; Chang, Hui Hua (Frontiers in Nutrition, 2025)
BackgroundDrug-resistant epilepsy (DRE) is a chronic neurological disorder with somatic impacts and an increased risk of psychiatric comorbidities and cognitive impairment. Previous studies suggested that genomic variants could contribute to the high interindividual variability in epilepsy and in its treatment response, but it remains unclear. Here, we aimed to perform genome-wide association study (GWAS), leverage the enrichment analysis of the genomic variants, and provide the potential molecular signature profiles. Moreover, we investigated the potential role of molecular signature profiles, as exemplified by tryptophan catabolites (TRYCATs), in DRE patients.MethodsWe used data from the Taiwan Biobank to perform a GWAS and identified enrichment pathways through the functional database Reactome. To validate the results, we enrolled community-dwelling controls and DRE patients. The levels of TRYCATs were determined using liquid chromatography–tandem mass spectrometry. In addition, we compared the levels of TRYCATs between the controls and DRE patients at baseline and after 6-month multivitamin supplementation. Seizure frequency was defined as the number of episodes per 28 days in DRE patients.ResultsUsing GWAS and enrichment analysis of genomic data, we obtained candidate genes implicated in mechanisms and molecular signature profiles against epilepsy, such as the TRYCATs pathway. To validate the molecular signature from enrichment analysis, we further examined whether the TRYCATs pathway was associated with the pathophysiology of epilepsy and treatment outcome in DRE patients. We found that DRE patients had significantly lower levels of TRYCATs (tryptophan, serotonin, 3-indole acetic acid, 3-indoleperopionic acid, kynurenine, and kynurenic acid) than the controls. Additionally, changes in the balance of the TRYCATs pathway were noted in DRE patients treated with 6-month multivitamin supplementation. Furthermore, the change levels of TRYCATs were correlated with seizure frequency in the DRE patients during multivitamin supplementation.ConclusionThe TRYCATs pathway plays an important role in the pathophysiology of epilepsy and is involved in the multivitamin-mediated physiological alterations in DRE patients. Therefore, the balance of TRYCATs might be a new biomarker and therapeutic strategy for epilepsy.